The Relationship Between Age and Parity With the Incidence of Anemia During Pregnancy - Shiny Ria Pratiwi; Fauzul Munah; Ninick Corea Fernandez; Bernadeta Erni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Anemia is a common problem in pregnant women. The prevalence of anemia according to the 2024 Indonesian Health Survey, the incidence of anemia in pregnant women in Indonesia reached 27.7%. In Lampung province, 10,214 pregnant women suffered from anemia. Factors that influence anemia in-clude age and parity. The aim was to determine the relationship between age and parity with the inci-dence of anemia in pregnancy. Research design: This type of research is analytical with a cross-sectional design, using the Chi-square test. The sample of this study was 110 pregnant women who were examined at PMB F in October-December 2025, with a total sampling technique. The instrument in this study used a recapitulation sheet. Data analysis used the Chi-square test. Research results: The results ob-tained 54 (49.1%) at-risk ages, namely <20 years and >35 years, 62 (56.4%) parity primiparas, and 47 (42.7%) pregnant women experienced anemia. Statistical tests revealed a relationship between age (p=0.000) and parity (p=0.000) and the incidence of anemia during pregnancy. Conclusion: There is a relationship between age and parity and the incidence of anemia during pregnancy.